Saponin Fraction CIL1 from Lysimachia ciliata L. Enhances the Effect of a Targeted Toxin on Cancer Cells - Paulina Koczurkiewicz-Adamczyk; Karolina Grabowska; Elżbieta Karnas; Kamil Piska; Dawid Wnuk; Katarzyna Klaś; Agnieszka Galanty; Katarzyna Wójcik-Pszczoła; Marta Michalik; Elżbieta Pękala; Hendrik Fuchs; Irma Podolak (MDPI AG, 2023)
Saponins are plant metabolites that possess multidirectional biological activities, among these is antitumor potential. The mechanisms of anticancer activity of saponins are very complex and depend on various factors, including the chemical structure of saponins and the type of cell they target. The ability of saponins to enhance the efficacy of various chemotherapeutics has opened new perspectives for using them in combined anticancer chemotherapy. Co-administration of saponins with targeted toxins makes it possible to reduce the dose of the toxin and thus limit the side effects of overall therapy by mediating endosomal escape. Our study indicates that the saponin fraction CIL1 of Lysimachia ciliata L. can improve the efficacy of the EGFR-targeted toxin dianthin (DE). We investigated the effect of cotreatment with CIL1 + DE on cell viability in a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, on proliferation in a crystal violet assay (CV) and on pro-apoptotic activity using Annexin V/7 Actinomycin D (7-AAD) staining and luminescence detection of caspase levels. Cotreatment with CIL1 + DE enhanced the target cell-specific cytotoxicity, as well as the antiproliferative and proapoptotic properties. We found a 2200-fold increase in both the cytotoxic and antiproliferative efficacy of CIL1 + DE against HER14-targeted cells, while the effect on control NIH3T3 off-target cells was less profound (6.9- or 5.4-fold, respectively). Furthermore, we demonstrated that the CIL1 saponin fraction has a satisfactory in vitro safety profile with a lack of cytotoxic and mutagenic potential.